Banking regulation in the United States after the world economic crisis of 2007/2008: economic immunity or false hopes - Freddo, Daniela; Nofal, Sulafa; Vargas, Juliano (Brazilian Keynesian Review, 2022)
Based on the Post-Keynesian approach, we argue that commercial banks, through the financial reforms of 1980 and 1999, which made financial institutions more flexible, increased their capacity to operate in the capital market by becoming Banking Financial Holding Companies. The 2007/2008 crisis is understood as a consequence of financial deregulation and financial innovation process that weakened the Federal Reserve’s capacity to restrain banking activity. Initially, we discuss the new institutional context that emerged from these changes in the financial regulatory framework between 1980 and 1999. Then, we focus on how financial deregulation allowed banking business to advance in financial markets, how this process contributed to the economic crisis of 2007, characterized both as a liquidity crisis and a solvency crisis, safeguarded by the National States. Finally, we analyze the Dodd-Frank Law (2010), which is interpreted as the reaffirmation of this endogenous process of financial domination.